PENINGKATAN KETERAMPILAN PEMUDA KARANG TARUNA DESA BEJI MELALUI PELATIHAN TEKNISI KOMPUTER - Gustin Setyaningsih; Ito Setiawan; Muhamad Awiet Wiedanto Prasetyo; Ranggi Prahraningtyas Aji; Nabila Aprilianti (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2019)
Karang Taruna aims to realize the growth and development of every member of society who is qualified, skilled, intelligent, innovative, characterized and has social awareness and responsibility in preventing, counteracting, overcoming and anticipating various social welfare issues, especially the younger generation, the quality of social welfare of each member the community, especially the younger generation in the village / kelurahan in an integrated, directed, comprehensive and sustainable manner, the development of business towards the independence of every member of the community, especially the younger generation and the development of partnerships that ensure increased capability and potential of young people in a directed and sustainable manner. This is reflected in the vision of cadets by Beji Village 5, namely: "Creating young people who are creative, innovative, productive and social" and one of the missions "Improving HR for a better future through the social field". One of the work programs is training for its members. This work program is under the coordinator of education and training. Community service activities in the form of computer technician training for administrators and members of Karangtaruna have been carried out. The knowledge of the management and members of Karangtaruna village of Beji regarding computer technicians in general increased compared to before conducting the training indicated by the results of the interview. With the training of computer technicians the management and members become aware of the name of the hardware, maintenance and trouble shooting associated with computer technicians.